Rethinking the medical in the medical humanities. Issue 2 (4th March 2016) - O'Neill, Desmond; Jenkins, Elinor; Mawhinney, Rebecca; Cosgrave, Ellen; O'Mahony, Sarah; Guest, Clare; Moss, Hilary
Abstract : To clinicians there are a number of striking features of the ever-evolving field of the medical humanities. The first is a perception of a predominantly unidirectional relationship between medicine and the humanities, generally in terms of what the arts and humanities have to offer medicine. The second is the portrayal of medical practice in terms of problems and negativities for which the medical humanities are seen to pose the solution rather than viewing medicine as an active and positive contributor to an interdisciplinary project. Paradigms that fail to recognise the contributions of medicine and its practitioners (including students) to the medical humanities, this paper argues, will continue to struggle with definition and acceptance. This paper explores the possibilities for advancing the medical humanities through recognition of the contribution of medicine to the humanities and the importance of engaging with the arts, culture and leisure pursuits of doctors and medical students. Our research shows the richness of cultural engagement of medical students, their broad range of cultural interests and their ability to contribute to research and scholarship in the medical humanities. Mutual recognition of strengths, weaknesses and differences of scholarly approach is critical to successful development of the enterprise. Recognising and building on the interests, sympathies and contributions of medicine and its practitioners to the medical humanities is a fundamental component of this task. Future directions might include introductory courses for humanities scholars in aspects of healthcare and medicine.